Economic Evaluation of Losses From Invalidism of the Population in Russia: Approaches and Methods - Olga I. Goleva (Финансы: теория и практика, 2017)
Topic. Economic evaluation of losses from invalidism of the population as an important component of a balanced decision-making in health and social policy (in particular, as concerns the programs of social well-being, adaptation and rehabilitation of invalided persons).Purpose. Analysis of modern approaches and methods of economic evaluation of losses from invalidism of the population (from the point of view of completeness and correctness of the assessment, applicability, taking into account peculiarities of statistical surveying in the Russian Federation).Methodology.On the basis of theoretical analysis of the legal and literature sources (the official Methodology of calculating economic losses from mortality, morbidity and invalidism of the population and the research articles presented in the RISC database from 2000 to 2016) we summarize the main approaches to economic evaluation of losses from invalidism of the population of the Russian Federation. There were also differentiated and formalized the main problems of economic evaluation of losses from disability.Results.There were analyzed different approaches and methods of economic evaluation of losses from invalidism of the population used in the Russian Federation. We identified and highlighted the advantages and disadvantages of considered methods. There were formulated conceptual and methodological problems of economic evaluation of losses from invalidism of the population (such as completeness and quality of baseline data, problems of evaluation of current and deferred direct and indirect losses (loss of production of the manufactured product), etc.).Conclusions. The main problems in the assessment of economic losses from invalidism in the Russian Federation at the present stage are the lack of disaggregated data on invalidated persons and lack of uniform and complete assessment techniques applicable for the purposes of comparison of costs and benefits by the state authorities. It is noted that the question of the adequacy and completeness of the data can be solved by using the Federal state information system “Federal register of disabled persons”, which is being introduced from 2017.